Literature Review Visualisasi Data dan Sistem Informasi Geografis - Famia Septa Dinda Alfia; Agussalim Agussalim (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
In the past, statisticians, programmers, and data scientists handled data analytics, rarely interacting with companies directly. However, this "experts only" method of data analysis and display has been altered by more user-friendly data visualization, dashboards, and mashup technologies. With improvements that make it possible for people at all levels of an organization to analyze data in meaningful ways, data analytics is being pushed into business. The reporting and visualization tools that statisticians formerly used are now being improved by manufacturers of enterprise-grade analytics. This study describes how dashboards help businesses optimize their operations. And how business dashboards are developed using real-time data and people's innate capacity for visual thought.